An Analysis of Affixation Found in Sasak Language in Kelayu Dialect: A Descriptive Study - Anisa Maulana Anggraini (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
In the development of language, there are many variations of language in society, this is because language is changing continuously, and it is changing in different places. One aspect of language that is interesting to research is affixation. Affixation is a morphological process in linguistics where affixes are added to the root of a word to form a new word. The study aimed at describing prefixes and suffixes that are exist in Kelayu dialect. This is research was descriptive qualitative research. It concerned in the uses of affixation found in Sasak language used by Kelayu villagers. There were three domains chosen. The first was family, second was friendship and third was neighborhood. The data were collected based on five instruments, namely: observation, recording, documentation study/documentation, word list, and note taking. The result of the study showed that there are 7 kinds of prefixes and 4 kinds of suffixes that are exist in Kelayu dialect. The prefixes are {be-}, {ke-}, {me-}, {ng-}, {nge-}, {pe-}, and {te-}. The suffixes were found are {-an}, {-ang}, {-in}, and {-ye}. There was also no indication of infix, it happened because there are no words influenced by infix.